Improved setting and hardening of fly ash geopolymer concrete cured at room temperature - Nath, Pradip; Sarker, Prabir (The University of British Columbia, 2015)
Fly ash based geopolymer is an emerging low-emission binder for concrete. Recent studies have shown that the properties of geopolymers are similar to those of the OPC binder traditionally used for concrete. Most previous studies in literature used heat curing to accelerate setting and hardening of fly ash geopolymer mixtures. Though heat curing is a common practice for making precast concrete products, it is an energy consuming process and may not be possible for cast-in-situ applications. This paper presents a study on making low calcium fly ash based geopolymer concrete to enable curing at low ambient temperature without additional heat. Small amount of ground granulated blast furnace slag (GGBFS) was added with fly ash. Setting times of geopolymer pastes, and workability and compressive strength of mortars were tested for samples cured at 20oC and at 30oC for 24 hours. Results show that, higher compressive strength was achieved when initial curing temperature was higher and when GGBFS was included in the mixture. Inclusion of GGBFS helped achieve reasonable setting time and enhanced compressive strength as compared to mixtures having fly ash only, without heat curing. The effect of concentration of alkaline solution was also investigated. When concentration of sodium hydroxide increased, compressive strength and setting time increased. The results suggest that suitable geopolymer mixtures can be designed for ambient curing using low calcium fly ash with GGBFS as a partial replacement.